2022
DOI: 10.37427/botcro-2022-002
|View full text |Cite
|
Sign up to set email alerts
|

Festuca albomontana (Poaceae), a new chasmophytic fescue from the Western Taurus Mountains (Antalya, Turkey)

Abstract: A new species of Festuca from the Western Taurus Mountains (Antalya, Turkey) is described here and named F. albomontana. The new species can clearly be distinguished from the other species included in the F. alpina group by its leaf anatomical features. It has a geographically isolated position in the Western Tauruses whereas a closely related species, F. sommieri, is very local in the Black Sea Region of Turkey. It is suggested that it should be in the “critically endangered” threat category according to the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 4 publications
0
1
0
Order By: Relevance
“…Therefore, Ellis (1976) indicated that anatomical data are regarded as being of undoubted importance in the jigsaw of complete systematic evidence. Leaf anatomical characters in cross-section have been the main supplementary tools to add to the morphological features for characterizing some genera of difficult taxonomy within the grass family (e.g., Ellis 1976, 1986, López and Devesa 1991, Martínez-Sagarra et al 2017, Aykurt et al 2022) such as Festuca L. (e.g., Martínez-Sagarra et al 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, Ellis (1976) indicated that anatomical data are regarded as being of undoubted importance in the jigsaw of complete systematic evidence. Leaf anatomical characters in cross-section have been the main supplementary tools to add to the morphological features for characterizing some genera of difficult taxonomy within the grass family (e.g., Ellis 1976, 1986, López and Devesa 1991, Martínez-Sagarra et al 2017, Aykurt et al 2022) such as Festuca L. (e.g., Martínez-Sagarra et al 2017).…”
Section: Introductionmentioning
confidence: 99%